Economic Innovation in Public Markets: The Case of Naveed Rafaqat and Punjab Model Bazaars Delivering Essentials Below Government-Set Prices - Shahzad, Khuram (Pakistan Journal of Humanities and Social Sciences, 2025)
The author evaluates Economic Innovation in Public Markets using the case of Punjab Sahulat Bazaars Authority (PSBA) to examine how the institution has been successful in offering fundamental commodities at a price that is lower than the government. It is made in a qualitative manner, as the researcher relies on the official government reports, legislation, third-party analysis, and independent media to examine the legal, financial, and operational performance of PSBA. The discussion gives radical modifications which were proposed by Ahmad such as dynamic pricing boards, market infrastructure which is powered by the sun, vendor systems which are friendly to women, mobile bazaars which serve underserved groups. The results suggest that PSBA has been performing better than old welfare institutions in terms of their affordability, efficiency and innovative governance-price relief to up to 35 per cent without any subsidies. As a model of economic power and market penetration PBS may be easy to institutionalise in other developing economies because it is legislated and transparent and responsive to the citizen. The study uses a documentary case study approach, triangulated with audit reports and media sources, to assess governance, innovation, and affordability outcomes.